HEALTH-RELATED QUALITY OF LIFE POST-SINOVAC VACCINE IN COMMUNITIES IN TAMPAN DISTRICT AND MARPOYAN DISTRICT, PEKANBARU CITY - Seftika Sari; Rickha Octavia; Novelia Sukista (Jurnal Farmasi Sains dan Praktis, 2023)
Giving the Sinovac vaccine for Covid 19 can cause several side effects. The existence of side effects that occur, of course, affect their lives, including a decrease in activity, productivity and quality of life. This study aims to determine the HRQoL score in the community after the Sinovac vaccine in Tampan District and Marpoyan District, Pekanbaru City. The research method is analytic observational with a cross-sectional design. The research sample was people who received the first vaccine recorded at the Puskesmas in Tampan District and Marpoyan District, Pekanbaru City, which was selected by purposive sampling technique according to inclusion and exclusion criteria and obtained a sample of 100 respondents. The instrument is a questionnaire EQ5D5L and EQ-VAS. The study results showed that there was little problem with the dimensions of pain (37%) and usual activities (14%), with a score of 0,944 (EQ5D5L) and 0,975 (EQ-VAS). In conclusion, the HRQoL scores on EQ5D5L and EQ-VAS are close to 1, which means close to perfect. This research is expected to be a reference for stakeholders in selecting preventive therapy for Covid 19 and can be used as initial data for cost-utility analysis research.